ANALISIS MODEL KELEMBAGAAN AGRIBISNIS BUAH NAGA ORGANIK, DESA JAMBEWANGI, KABUPATEN BANYUWANGI - Bachtiar, Riza Rahimi; Holik, Abdul; Widakdo, Danang SWPJ (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2020)
The development of leading commodity agribusiness centers was an initial activity to develop economic area, especially in Banyuwangi. One area in Banyuwangi that had great potential in the development of the dragon fruit agribusiness center was Jambewangi. The implementation of this organic dragon fruit farming system had various advantages including: the price of dragon fruit could be sold higher, environmentally friendly, and healthy. However, there were several problems in Jambewangi, such as the marketing system of organic dragon fruit still not optimal because farmers could not directly sell the dragon fruit to consumers. Organic dragon fruit farmers must deposit their harvests to middlemen (collector traders), therefore the benefits were not optimal. Another problem was dragon fruit as a perishability, seasonal, requires a lot of space, and not uniform. The various problems above caused the need for an institutional design model of organic dragon fruit agribusiness to increase farmer’s incomes. This study was aimed to design and analyze the institutional model of organic dragon fruit agribusiness in Jambewangi, Banyuwangi. The sampling method used in this study was the Snowball Sampling method. The results showed that the organic red dragon fruit trading system in Jambewangi consisted of: a) Farmers - Village Collector Traders - Regency Collector Traders - Supermarkets - Consumers. b) Farmers - Regency Collector Traders - Supermarkets - Consumers. c) Farmers - Village Collector Traders - Retailer Traders - Consumers. d) Farmers - Retailers - Consumers. e) Farmers - Regency Collector Traders - Retailer Traders - Consumers. f) Farmers - Regency Collector Traders - Consumers. g) Farmers - Consumers. The most efficient trading system channel was Channel 7, which is marketing organic dragon fruit from farmers and then channeled directly to consumers.